Social Community in Sarajevo in 18th Century : About the Non-muslim Population in Medjmua of Mula Mustafa Bašeski (Prilozi za orijentalnu filologiju, 2017)
The starting point for this paper are the notes where the non-Muslim population was mentioned in a medjmua (notebook) which was written from 1757 to 1804 by Mula Mustafa Bašeski. By the analysis of these notes, collected from different pages of Bašeski’s notebook, the writer’s understanding of the status of non-Muslims in a social community organized by Islamic law is being understood. Through the concrete examples from the text it is shown how Mula Mustafa Bašeski expects people to take care of the community they belong to, and, likewise, from the social community to take care of its members. The paper shows how the author’s personal attitude to non-Muslim citizens could be clearly read from the notes in necrologue – the part of the notebook where he recorded the deaths of his acquaintances and friends in order to test his piety. The purpose of this paper is to show through the words and actions of a contemporary the life in the Sarajevo social community in 18th century. The paper includes notes where Mula Mustafa wanted to point out certain moral values, and in which the non-Muslim population was mentioned on various occasions.